Influence of softer binder and rejuvenator on bituminous mixtures containing reclaimed asphalt pavement (RAP) material - Sujit Kumar Pradhan; Umesh Chandra Sahoo (International Journal of Transportation Science and Technology, 2022)
Use of the recycled asphalt pavement (RAP) material is necessary for the sustainable development of the road infrastructure. However successful incorporation of RAP in hot mix asphalt (HMA) has been only up to 30%. Considering the pressing need for higher utilization of RAP, the present study explores the performance of recycled HMA produced by incorporating Polanga oil as rejuvenator and also with softer binders separately for comparison purposes. A total of eleven mixes were designed, out of which there is control mixture with PG 70-X, five mixtures containing varying percentages of RAP (30–70) added with the softer binder and another five containing the same variation in RAP with a rejuvenator (its content fixed at 5% by mass of RAP binder). The effects of the softer binder and rejuvenator on the recycled asphalt mixtures were analyzed in terms of volumetric, indirect tensile strength (ITS), moisture susceptibility, rutting, intermediate temperature cracking, and resilient modulus. Thermogravimetric analysis (TGA) was performed to see the thermal stability of the rejuvenator, which showed that the rejuvenated binder is stable up to 230 °C which is more than the asphalt mixing temperature. Results also inferred that up to 60% RAP can be successfully incorporated into the HMA with the addition of a softer binder or a rejuvenator, without compromising the performance significantly.